Exploring Digital Assets Inheritance: A Comparative Study of Transnational Legal Frameworks and Practices - Yolanda, Maureen Keisha; Paramitha, Chintya Lie; Putra, Moody Rizqy Syailendra (CV. Rayyan Dwi Bharata, 2025)
Digital Assets Inheritance also can be defined the same as the inheritance itself. What makes the Digital Assets Inheritance different is the assets would be inherited. Digital Assets is anything that is owned in the form of digital rather than a physical one. Digital Assets could include; Social media accounts, Digital photos and videos, Loyalty points, Websites, E-book, and so on. Digital assets vary a lot in terms of both type and value. Some types might only have sentimental value, such as photos or family videos. Others might have significant monetary value, such as cryptocurrency, monetised social media accounts or unpublished manuscripts. Legally speaking, anything that a person owns becomes part of their estate when they die. This includes digital assets. Personal representatives should be able to access digital assets in order to access and distribute them among beneficiaries. However, this is not always straightforward in practice. If the person who has died has not left instructions on how to log in or to access digital assets, their personal representatives will have to follow the policies of each company with whom the person who has died had an account. These policies will not necessarily make it possible for loved ones to access accounts, which can mean that digital assets of sentimental value such as emails, photographs and written text might be lost. Planning in advance for these eventualities can avoid this. When you make a Will, you can choose to include instructions on how to access your digital accounts after your death. Some digital accounts also allow you to add a ‘legacy contact’ or ‘inactive account manager’ who would be authorized to manage your account should you no longer be able to.